Association of VitamÄ±n D Deficiency and Respiratory Syncytial Virus with Severe Lower Respiratory Tract Infection in Newborn Intensive Care Unit - Tüfekci, Sinan; Aygün, Erhan (Archives of Clinical and Biomedical Research, 2020)
Background: Newborn infants are exposed to life-threatening conditions such as severe lower respiratory tract infections mostly caused by a respiratory syncytial virus. Previous studies suggest vitamin D deficiency is associated with an increased risk of lower respiratory tract infections but this hypothesis is controversial. This study aimed to assess the relationship between serum vitamin D levels and the occurrence of lower respiratory tract infections among Turkish infants. Methods: We performed a case-control study including newborns admitted in the neonatal intensive care unit. Respiratory syncytial virus related respiratory infections were confirmed by the Respi-strip test. Clinical and biological data were collected from medical records and analyzed with Epi Info7. Results: We included 18 newborns (9 cases with the diagnosis of respiratory syncytial virus-related lower respiratory tract infections and 9 controls admitted with another diagnosis). Their mean age was 23.72 days and sex-ratio was 2. The main clinical symptoms of lower respiratory tract infections were cough, tachypnea, and fever and respiratory syncytial virus test was positive in all cases. Vitamin D level was significantly lower in cases compared to the control group (5.40 vs 17.67 ng/ml respectively). All newborns with lower respiratory tract infections presented vitamin D deficiency and 11.1 % of controls had normal vitamin D status. All babies and mothers with vitamin D deficiency were supplemented. Conclusions: Our results suggest that severe lower respiratory tract infections is associated with lower vitamin D levels among newborns admitted in neonatal intensive care unit. Vitamin D supplementation could help correct this deficiency and prevent postnatal severe lower respiratory tract infections.